The Effect of Financial Literacy, Financial Technology, Lifestyle and Religiosity on Consumptive Behavior Among University Students - Giyarda Maulana; Nawalin Nazah; Wida Purwidianti; Purnadi Purnadi (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of financial literacy, financial technology, lifestyle, and religiosity on the consumptive behavior of students at Universitas Muhammadiyah Purwokerto. A quantitative approach with a survey method was employed. Data were collected from 434 respondents selected through proportional sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy, financial technology, and lifestyle have a positive and significant effect on consumptive behavior, while religiosity has no significant effect. Lifestyle is the most dominant variable influencing consumptive behavior, and the research model explains 55.3% of the variance in consumptive behavior. These findings indicate that students’ consumptive behavior in the digital era is more strongly influenced by technological and lifestyle factors than by religiosity. The study provides practical implications for higher education institutions in strengthening behavior-oriented financial education and for financial technology providers in enhancing spending control features.